(3GdPcGA GdUfGYj aj dZI (BProlog (3hehGVjY aj GdCfXeI GdNHjQIs - (3GdRQbG, RjfHs; (3YhOI, Cjefs ((3MdHs (3TYGY ddfTQ hGdYdhes, 2005)
(3jJVef gPG GdcJGH TQhMkG JaUjdjI eOYheI HGdCeKdI dcGaI echfGJ dZI (BProlog(3, EVGaI Edi TQM JbOjej dHjFI GdJWhjQ GdeQFjI d` (BVisual Prolog ver. 5.2s
1
Keywords: (3GdHQeLIs; (3GdMGSHGJ GdEdjcJQhfjIs -- (3dZGJs